Analisis Terhadap Math Anxiety Siswa SMP berdasarkan Gender pada Masa Pandemi Covid-19 - Saskia Tomigolung; Sonya F Tauran (LPPM Universitas Advent Indonesia, 2021)
This research aims to determine how the students’ math anxiety based on gender during the covid-19 pandemic. The respondents of this research are 200 students of SMP Advent Unklab Airmadidi Manado. The data collection technique applied is the math anxiety questionnaire. The method of this research is a quantitative method. The results show that mean of male students’ math anxiety is equal to 60,20% while for female students is equal to 58,92%. The results also show that math anxiety of male students is not higher or equal to math anxiety of female students. The aspects of math anxiety, namely the cognitive, affective, psychomotor and somatic aspects of male students are not higher or equal to female students.